The politics of exclusion debating migration in Austria - Krzyżanowski, Michał 1977-; Wodak, Ruth 1950- (Transaction Publishers, 2008)
The production and re/production of institutional and everyday racism towards migrants : the role of discourse -- Austrian politics and migration-related legislation -- Migration-related developments in Austria : historical, demographic, and economic dimensions -- The outside perspective : migration and Austrian public discourse -- The inside perspective : experiences of migrants in Austria -- Conclusions.
Includes bibliographical references and index
Keywords: Migration; Minderheit; Emigration and immigration -- Austria; Minorities -- Austria; Racism -- Austria; Discrimination -- Austria; Rassismus; Fremdenfeindlichkeit; Österreich; Austria -- Race relations